2018
DOI: 10.1536/ihj.17-492
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Early Diagnosis of Cardiac Sarcoidosis in Patients with Complete Atrioventricular Block

Abstract: Our aim is to clarify the factors for early diagnosis of cardiac sarcoidosis (CS) in patients with complete atrioventricular block (CAVB) and its impact on cardiac function after corticosteroid therapy.A total of 15 CS patients with CAVB who underwent corticosteroid therapy were retrospectively analyzed. Patients were divided into two groups according to the time from the first CAVB onset to the diagnosis of CS. Clinical characteristics and outcomes were compared between the early diagnosis group (within 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Early recognition and treatment of underlying CS can prevent progressive LV dysfunction, reduce morbidity and mortality as well as prevent unnecessary device upgradation or cardiac transplantation. Some authors [5,11,12] have also reported similar cases, where underlying CS rather than PICM which was responsible for progressive LV dysfunction. It is indeed difficult to suspect CS among patients diagnosed of PICM as majority of do not have systemic involvement.…”
Section: Discussionmentioning
confidence: 91%
“…Early recognition and treatment of underlying CS can prevent progressive LV dysfunction, reduce morbidity and mortality as well as prevent unnecessary device upgradation or cardiac transplantation. Some authors [5,11,12] have also reported similar cases, where underlying CS rather than PICM which was responsible for progressive LV dysfunction. It is indeed difficult to suspect CS among patients diagnosed of PICM as majority of do not have systemic involvement.…”
Section: Discussionmentioning
confidence: 91%
“…This is comparable with a previous report including CS patients presenting with a complete AV-block, where in none of the patients with delayed diagnosis 67 Ga Scintigraphy and/or 18 F-FDG-PET was performed. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Last, the diagnosis might be confirmed by positive extracardiac histology with cardiac symptoms, but extracardiac symptoms are frequently absent. 3 , 19 However, despite absence of extracardiac complaints or involvement, it can be worthwhile to perform additional pulmonary diagnostic testing. A mediastinal lymphnode biopsy and/or bronchoalveolar lavage confirmed diagnosis in 84% of patients with suspected CS without extracardiac complaints, regardless of imaging findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the primary role of immune‐suppression is secondary prevention of cardiac dysfunction and ventricular arrhythmias. Efficacy of corticosteroid therapy is enhanced in early stage CS with well‐preserved ventricular systolic function . However, the urgent initiation of immune‐suppression is often delayed due to the technical difficulty of obtaining histopathological evidence required in conventional guidelines.…”
Section: Discussionmentioning
confidence: 99%